2000
DOI: 10.1029/1999je001086
|View full text |Cite
|
Sign up to set email alerts
|

Local and regional lunar regolith characteristics at Reiner Gamma Formation: Optical and spectroscopic properties from Clementine and Earth‐based data

Abstract: Abstract. A detailed remote sensing survey of the Reiner Gamma Formation (RGF) region by means of Earth-based telescopic and Clementine multispectral imaging has been made in the UVvisible-near-infrared domain. The spectral mixture analysis reveals the existence of three basic end-members relevant for modeling the observed spectral variations in the RGF vicinity. These are MB (mare background), SWS (southwest swirl), and RGS (Reiner Gamma soil). The first two components exhibit spectral characteristics consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 41 publications
6
86
2
Order By: Relevance
“…The same can be said about the swirl Reiner Gamma, where some excess of CPx is observed in comparison with the surrounding mare regions. This agrees well with the age of the swirl: it is one of the youngest formations on the lunar surface (Pinet et al, 2000;Starukhina and Shkuratov, 2004). The soil in the South Pole-Aitken basin (the lower corners of the mosaic) contains a lot of CPx.…”
Section: Resultssupporting
confidence: 73%
“…The same can be said about the swirl Reiner Gamma, where some excess of CPx is observed in comparison with the surrounding mare regions. This agrees well with the age of the swirl: it is one of the youngest formations on the lunar surface (Pinet et al, 2000;Starukhina and Shkuratov, 2004). The soil in the South Pole-Aitken basin (the lower corners of the mosaic) contains a lot of CPx.…”
Section: Resultssupporting
confidence: 73%
“…The mid-infrared Diviner data presented here place tight constraints on the swirl formation process and must be accounted for by any proposed swirl formation mechanism. The proposed feldspathic dust lofting 7 , meteoroid/comet swarm [4][5][6] and hybrid 41 swirl formation mechanisms would likely result in thermophysical and spectral properties that are inconsistent with the Diviner measurements. The proposed dust lofting and hybrid processes cannot account for the observed CF shift in Diviner data while the meteoroid/comet swarm and hybrid processes cause regolith disturbance that would result in a substantial thermal anomaly in the night-time Diviner data.…”
Section: Article Nature Communications | Doi: 101038/ncomms7189mentioning
confidence: 93%
“…Discussion Previous spectroscopic observations of the swirls at visible and near-infrared wavelengths have been used to argue for the solar wind standoff model 3,14,24 , the micrometeoroid/comet swarm model [4][5][6] or the feldspathic dust pile model. More recently, M 3 spectra have been used to propose a hybrid model for swirl formation that invokes both regolith disturbance and dust lofting 41 .…”
Section: Article Nature Communications | Doi: 101038/ncomms7189mentioning
confidence: 99%
See 1 more Smart Citation
“…The features are distinctive due to their fluid or wispy structure that is unlike either craters or impact ejecta. Their form has been determined to be unrelated to geographical topography and appears to overprint on both mountainous and plateau terrains (Bell & Hawke 1987;Pinet et al 2000;Blewett et al 2007). Although not all magnetic field anomalies have identifiable lunar swirl patterns, no lunar swirls have been found that are not coincident with similarly sized areas of anomalous crustal magnetic field (Blewett et al 2007;Kramer et al 2011a).…”
Section: Lunar Swirls and Magnetic Anomaliesmentioning
confidence: 99%